Etnobotani Tumbuhan dalam Makanan Tradisional Pecel di Desa Sumbermulyo Kecamatan Jogoroto Kabupaten Jombang Jawa Timur - Mucharommah Sartika Ami (KH. A. Wahab Hasbullah University, 2019)
Plants cannot be separated from everyday human life, including in terms of meeting food needs. Interactions between humans and plants were studied in ethnobotany. This study aims to determine the types and parts of plants used in traditional cuisine Pecel in the village Sumbermulyo sub-district Jogoroto, Jombang, East Java. The methods used were interviews and direct observation. The interview method was conducted in a semi-structured manner with the respondents determined through purposive random sampling technique. Direct observation was carried out to identify the types and parts of plants used in traditional food Pecel based on the results of the interview. The data obtained were then analyzed descriptively. The results showed that there were 16 plants species used in traditional food Pecel in Sumbermulyo village. Various plants, among others Allium sativum, Capsicum anuum, Capsicum frutescens, Citrus hystrix, Vigna radiata, Vigna sinensis, Arachis hypogaea, Ipomoea reptans, Cocos nucifera, Ocimum sanctum, Cucumis sativus var krai, Cucumis sativus, Oryza sativa, Carica papaya, Musa sp., dan Sesbania grandiflora. Plant parts used were buds, stems, leaves, flowers, fruits, seeds, and bulbs.